PSYCHOPATHIC PERSONALITY DISORDER IN LARSSON’S “THE GIRL WITH THE DRAGON TATTOO” - Tisnawijaya, Christy; Astuti, Puji (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
This paper investigates how childhood trauma causes someone to suffer from a personality disorder. The narrative discussed in this paper is The Girl with the Dragon Tattoo by Stieg Larsson (2005). The main character of the story, Martin Vanger, is unable to comprehend other’s feelings and gets pleasure from hurting women. These psychopathic behaviors are triggered by the traumatic events he endured during childhood. He was sexually assaulted by his father and was forced to watch him killing women. These experiences are the seeds of crimes that Martin commits as an adult. By using descriptive analysis, this paper explores how Martin, who was once a victim of child abuse, turns into the abuser. Freud states that someone’s personality is influenced by the interaction of id, ego, and super-ego (1993). Furthermore, Erikson believes that someone’s personality is also shaped by nature and nurture (1977). Therefore, psychoanalysis theory along with psychological approach is applied to examine the character’s psyche, mainly to reveal the causes of psychopathic personality disorder suffered by the main character. The result shows that traumatic experiences during childhood generate anxiety; guilt, shame, and agony affect the character’s psychosocial development.